An Examination of Parasitic Processes in DC/DC Power Converters - Jankovskis, J.; Stepins, D. (Elektronika ir Elektrotechnika, 2006)
Parasitic processes related to the magnetics of DC/DC converter − power inductors and interconnections (having inherent inductances) are studied by the use of buck converter. The study involves both experimental measurements and PSPICE simulation approaches. The results show that there is ringing having two components. The one, in the form of short duration spikes arises from discharge of self-capacitance of the power inductor. Another, in the form of high frequency ringing process arises from parasitic resonances set out mainly by capacitances of semiconductor devices and parasitic inherent inductances of the interconnections. Ill. 4, bibl. 13 (in English; summaries in English, Russian and Lithuanian).